The influence of biological aspects on the failure of treatment of dental implants with bone graft: literature review (Research, Society and Development, 2023)
Nowadays, the use of bone grafts in implant dentistry is part of an extremely predictable and widespread rehabilitation possibility for the constant replacement of missing teeth in cases of bone insufficiency. However, a complex of factors can make the treatment impossible and corrupt, favoring its failure, that is, despite the assured benefits, biological and mechanical complications can occur, compromising the stability of the rehabilitation. Thus, the aim of this study is to discuss the influence of biological aspects of bone grafts on failure in the treatment of dental implants. The present study was carried out through a narrative literature review based on articles searched in SciELO, Google Scholar and PubMed. The subsequent steps were through the definition of the topic addressed, selection of inclusion and exclusion criteria, bibliographic survey according to the selected databases and synthesis in writing the referred review. 22 selected articles were obtained from the initial search of 211 articles, in which reports obtained from the selected studies clarify that there is a significant association between implant failure and bone grafting procedures. Therefore, factors such as local conditions of the host site, bone unavailability, quality of the biomaterial used, systemic changes, osseointegration and vascularization, can interfere with the quality of installation and success of treatment with implants in grafted areas.